Buddhist Hybrid Sanskrit: How Did It Originate? - Hock, Hans Henrich (Bhasha)
Since Edgerton 1953, Buddhist Hybrid Sanskrit (BHS) has been considered a sanskritization of Prakrit, based on strong linguistic evidence: lexical items are Sanskritic, endings Prakritic. Sanskritization has been argued as motivated by a need to compete with Sanskrit-using brahmins. The issue of how sanskritization might have been accomplished is the topic of this paper. In early AD, Sanskrit was spread by brahmins as language of technical and fine literature. The curriculum of schools imparting Sanskrit instruction started with memorization of a Sanskrit lexicon and a version of Pāṇini’s grammar. The link between these was established in later years. Sanskritization of BHS can be explained in terms of early Buddhist students only completing the initial stage of instruction. This would provide them with a Sanskrit lexicon for replacing Prakrit words. However, not yet knowing how to apply the grammatical rules, students would use Prakritic endings. Support for this hypothesis comes from Kapstein’s (2018) account of grammatically deficient, but lexically accurate Sanskrit compositions by medieval Tibetans, as resulting from acquiring grammar and lexicon separately, ‘with almost no training in practical application’. I conclude by considering the implications of my proposal as well as the similarities and differences between BHS and ‘Bilingual Mixed Languages’.